Dengue Fever induced Myocarditis - Shareef, Adnan; Anam, Ahmad Mursel; Islam, Zahirul; Rabbani, Raihan (Bangladesh Critical Care Journal, 2016)
Dengue is an arthropod-borne viral illness, mostly asymptomatic, but may present with a wide variety of clinical manifestations, from mild febrile illness to severe and fatal disease. Cardiac involvement is a significant yet under-reported one because of lack of awareness. We report a case of myocarditis in Dengue Fever with an intention to create awareness among the physicians. Bangladesh Crit Care J September 2016; 4 (2): 125-127